Recent advances in aptamer-based targeted drug delivery systems for cancer therapy - Gao, Fei; Yin, Jianhui; Chen, Yan; Guo, Changyong; Hu, Honggang; Su, Jiacan (Frontiers in Bioengineering and Biotechnology, 2022)
The past decade has become an important strategy in precision medicine for the targeted therapy of many diseases, expecially various types of cancer. As a promising targeted element, nucleic acid aptamers are single-stranded functional oligonucleotides which have specific abilities to bind with various target molecules ranging from small molecules to entire organisms. They are often named ‘chemical antibody’ and have aroused extensive interest in diverse clinical studies on account of their advantages, such as considerable biostability, versatile chemical modification, low immunogenicity and quick tissue penetration. Thus, aptamer-embedded drug delivery systems offer an unprecedented opportunity in bioanalysis and biomedicine. In this short review, we endeavor to discuss the recent advances in aptamer-based targeted drug delivery platforms for cancer therapy. Some perspectives on the advantages, challenges and opportunities are also presented.